Maxillary length in 11‐ to 26‐week‐old normal fetuses studied by 3D ultrasound. (12th March 2015) - Hermann, N. V.; Darvann, T. A.; Sundberg, K.; Kreiborg, S.; Joergensen, C.
Abstract Objectives The objective of this article is to investigate normal prenatal maxillary length using 3D ultrasound and to correlate this with previously reported results for the mandible and the biparietal diameter (BPD). Methods Seventy‐two 3D ultrasound volumes from normal pregnancies in 52 volunteers (gestational age: 11–26 weeks) were obtained using a GE Voluson 730 Expert 3D scanner. Maxillary length and BPD were measured. Growth velocity and rate were calculated. Maxillary values were correlated with BPD and previously reported mandibular values. Results The mean total maxillary length ranged from 7.4 ± 2.7 mm at 11 weeks to 33.1 ± 2.7 mm at 26 weeks. Maxillary growth velocity can be described using a linear model. The correlation between maxillary and mandibular length, and BPD was high (R = 0.85–0.88). There was no statistically significant difference in the growth velocity between maxilla and mandible, whereas the velocity of the increase in BPD growth was significantly larger than that of the jaws. However, the growth rate was larger for the jaws than for the BPD. Conclusions Normative measures for the maxilla in 11‐ to 26‐week‐old fetuses are presented. Change in maxillary length was described using a linear model. The maxillary and mandibular growth velocities and rates were similar but differ from those of the BPD. © 2015 John Wiley & Sons, Ltd.